The Influence of Psychological Empowerment and Ethical Leadership on Work Engagement in PDAM Way Rilau Employees - Anjar Ahmadi; Yuningsih Yuningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
PDAM or Regional Drinking Water Company is one of the local business units in Bandar Lampung. owned by the city of Bandar Lampung, which has a role to distribute clean water to the public. distribute clean water to the general public. The problem in This research is the lack of work engagement which is influenced by the attendance in the month of November 2023 which is not maximized and is proven by attendance in November 2023 which has not been maximized and is evidenced by the data of the work performance assessment list in the with the data of the assessment list for the implementation of work in the obedience section only experienced an increase of 0.32 per year, which is relatively small for a yearly scale increase and the occurrence of the for an increase in the scale per year and the occurrence of a change in leadership leadership turnover in 2022 so that this is the focus of researchers to see psychological empowerment by new leadership on the work engagement of PDAM Way Rilau employees. This research aims to determine the effect of psychological empowerment and ethical leadership on employee engagement of PDAM Way Rilau. The study population was 253 people and the sample was taken as many as 156 people. Data collection through questionnaires based on random sampling technique and processed using Multiple Linear Regression Analysis with the help of SPSS software. SPSS software. The results of the study showed that psychological empowerment (X1) and ethical leadership (X2) have a positive and significant effect on work engagement (Y), thus the hypothesis of this study is supported.the hypothesis of this study is supported.